(untitled) (Research, Society and Development, 2022)
Objective: Verify whether lower preoperative serum albumin levels in cardiac surgery patients increase the incidence of acute kidney injury (AKI), pneumonia, postoperative stay in hospital and mortality. Methodology: A hundred and eighty-five medical records of patients that underwent cardiac surgery between January 2014 and December 2017 were surveyed. The albumin levels were compared between the group that presented at least one of the complications listed above and the group where that complication was not observed. The KDIGO criterion was used to define AKI. Pneumonia diagnosis was established based on clinical, radiologic and laboratory results. The postoperative time in hospital was considered increased when the patient had to stay for a period longer than 8 days. The mortality rate was defined by deaths that occurred up to 30 days after the surgery. Results: Albumin levels ≤3.87 mg/dL were associated to an increase in the risk to develop AKI (p= 0,0072). Albumin values ≤3.91 also increased the chance to have pneumonia (p= 0.0001). However, albumin was not statistically significant to predict mortality and increase in the postoperative stay in hospital. Conclusion: Serum albumin levels that were lower than or equal to 3.91 mg/dL and 3.87 mg/dL increased, respectively, the chances of developing both pneumonia and acute kidney injury after cardiac surgery. No significant results were obtained regarding albumin levels influence on postoperative stay in hospital or mortality.